Green Human Resource Management to Improve Competitive Advantage Through Organizational Citizenship Behaviour for Environment - Johan Oscar Ong; Masyudzulhak Djamil MZ; Eny Ariyanto; Sugiyono Sugiyono (Universitas Mercu Buana, 2022)
Competitive advantage is one of the important aspects that must be owned by companies in a competitive market. Human resource management is one of the important things in the development of the company. The research focuses on human resource management based on environmental management, namely green HRM to create competitive advantage through employee behavior voluntarily to care for the environment or what can be called Organization Citizenship Behavior for Environment (OCBE). Literature study is used to see the relationship of each variable, the results of the analysis of previous research that examines green HRM, OCBE and competitive advantage. Research shows that environmental care behavior of employees voluntarily towards the environment is influenced by environmental-based HR management in the company and this affects the company's competitive advantage.